Mutation Update of the CLCN5 Gene Responsible for Dent Disease 1. Issue 8 (11th June 2015) - Mansour‐Hendili, Lamisse; Blanchard, Anne; Le Pottier, Nelly; Roncelin, Isabelle; Lourdel, Stéphane; Treard, Cyrielle; González, Wendy; Vergara‐Jaque, Ariela; Morin, Gilles; Colin, Estelle; Holder‐Espinasse, Muriel; Bacchetta, Justine; et al.
<x xml:space="preserve">Abstract</x> We review previously reported mutations in the CLCN5 gene (Dent disease 1) and describe phenotype, novel (n=42) and recurrent mutations (n=24) in a large cohort of 117 patients belonging to 90 families. The novel missense and in‐frame mutations were mapped onto a three‐dimensional homology model of the ClC‐5 protein: this analysis suggests that these mutations affect the dimerization process, helix stability or transport. The phenotype of our cohort patients supports and extends the phenotype previously reported in smaller studies.